National Civic Federation records - National Civic Federation
Correspondence, memoranda, reports, press releases, newspaper clippings, printed matter, broadsides, and other records relating primarily to the work of the organization in promoting moderate progressive reform, resolving disputes between industry and organized labor, and combating communism. Subjects include anarchism, communism, socialism, the New Deal, industrial relations, labor unions, riots, antisemitism, and economic and political conditions in the Soviet Union. Other topics include African Americans, the National Hunger March on Washington, D.C., in 1931, and the Protocols of the Wise Men of Zion. Includes material pertaining to organizations such as the Communist International, Communist Party of the United States of America, Young Communist League of the U.S., and the American Youth Congress. Correspondents include Ralph M. Easley, executive board chairman, and his wife, Gertrude Beeks.
In part, positive photocopies and typewritten transcripts.
American economic organization composed of representatives of business and organized labor as well as consumer advocates. Favored moderate progressive reform and sought to resolve disputes arising between industry and organized labor. Founded in 1900; dissolved 1950.
Collection material in English, with Russian.
Keywords: Beeks, Gertrude, -- 1867- -- Correspondence; Easley, Ralph M. -- 1858- -- Correspondence; American Youth Congress; Communist International; Communist Party of the United States of America; Young Communist League of the U.S.; Protocols of the wise men of Zion; African Americans; Anarchism -- United States; Antisemitism -- United States; Arbitration, Industrial -- United States; Communism; Communism -- Societies, etc; Communism -- United States; Industrial relations -- United States; Jews -- United States; Labor movement -- United States; Labor policy -- United States; Labor unions -- United States; New Deal, 1933-1939.; Riots -- United States; Socialism -- United States; Youth -- United States -- Societies and clubs; Soviet Union -- Economic conditions -- 1917-1945.; Soviet Union -- Politics and government; United States -- Economic conditions -- 1918-1945.; United States -- Economic policy -- 20th century; United States -- Politics and government -- 1901-1953.; United States -- Social conditions -- 20th century; United States -- Social policy -- 20th century